Synthesis and Spectroscopic Studies of Some Metal Complexes of (4-Nitrobenzoyl) Carbarmothioyl) Histidine (NCH) - Athraa Gazi (Journal of Global Pharma Technology, 2018)
(4-nitrobenzoyl) carbamothioyl) histidin (NCH) a new ligand was synthesized by reaction of Histidine with (4-Nitrobenzoyl isothiocyanate) by using acetone as a solvent. The prepared ligand (NCH) has been characterized by elemental analysis (CHNS), infrared (FT-IR), electronic spectral (Ultraviolet visible) and (1H, 13C-Nuclear Magnetic Resonance) spectra. Some Divalent metal ion complexes of (NCH) were prepared and spectroscopic studies by Fourier transform infrared (FTIR), electronic spectral (UV-Vis), molar conductance, magnetic susceptibility and atomic absorption.  The results measured showed the formula of six prepared complexes were [M (NCH) 2]    (M+2 =Manganese, Cobalt, Nickel, Zinc, Cadmium and Mercury), from the obtained data tetrahedral structure suggested for all complexes, except Copper complex has a square planer geometry.Keywords: Histidin, Metal Ion complexes, 4-Nitrobenzoyl isothiocyanate.